Parental involvement and the intergenerational transmission of economic preferences, attitude and personality traits - Maria Zumbuehl; Thomas Dohmen; Gerard A. Pfann (University of Bonn and University of Cologne, Reinhard Selten Institute (RSI), 2020)
We empirically investigate the link between parental involvement and shaping of the economic preferences, attitudes and personality traits of their children. We exploit information on the risk and trust attitudes, the Big Five personality traits and locus of control of parents and their children, as well as rich information about parental efforts in the upbringing of their children from the German Socio-Economic Panel Study. Our results show that parents who are more involved in the upbringing of their children have children with more favourable attitudes and traits. These children rank higher in traits that further their success in life, and they are more similar to their parents in those attitudes, where the optimum level is more ambiguous.
Keywords: D9; Z1; J13; J62; 330; Risk preferences; trust; intergenerational transmission; cultural transmission; social mobility; SOEP